Effect of calcium hydroxide filler on mechanical poperties of natural rubber latex films (Journal of Rubber Research, 2012)
Calcium hydroxide dispersion was prepared by reacting calcium chloride (CaCl2) with sodium hydroxide (NaOH), at room temperature for one hour. The resulting dispertion was added to prevulcanised natural rubber latex compound indifferent amounts. The effects of calcium hydroxide loading on the viscosity of the prevulcanised latex, the crosslinking density of the latex films were investigated. Results showed that viscosity of the compounds decreased when calcium hydroxide was added. The modules at 100;elongation and at 300;elongation increased with calcium hydroxide loading. The tensile and tear strength increased up to 10 p.h.r of calcium hydroxide loading and then decreased again. The elongation at break, on the other hand, was not significantly affected by calcium hydroxide loading. The normal films showed properties in between that of the leached and aged films. SEM micrographs showed formation of agglomerates as calcium hydroxide content was increased.
Keywords: Calcium hydroxide; Filler; Latex; Mechanical properties; NR latex film